ANALISIS RISK DAN RETURN SAHAM LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE FEBRUARI 2009 – JANUARI 2014 - B11110098, GUNTUR (Jurnal Manajemen Update, 2014)
This research aims to know describe risk and return stock of LQ-45 listed at the Indonesian Stock Exchange period February 2009 - January 2014. Research sample taken based on companies which hold shares in stock of LQ-45 during the research period, of which 21 companies studied there are AALI, ADRO, ASII, BBCA, BBNI, BBRI, BDMN, BMRI, INCO, INDF, INTP, ITMG, JSMR, KLBF, LPKR, LSIP, PGAS, PTBA, TLKM, UNTR and UNVR.In this research used the Capital Asset Pricing Model (CAPM) for data analysis. The results of research indicate that all of the return company's stock indicates a positive value. The highest average return obtained by KLBF stock while the smallest average return obtained by INCO stock. In addition, in terms of risk calculated by using standard deviation, stocks that earned the biggest risk is INCO stock while the smallest risk is TLKM stock. When seen from beta, all of beta is positive and significant at α 5%. From 21 samples, there are 10 companies that have more than one beta value (β> 1) the company are BBNI, BMRI, BBRI, ASII, UNTR, INCO, ITMG, INDF, KLBF and PTBA it means that stock have charactersitic of aggressive, whereas the remaining 11 companies who value a beta of less than one (β <1) the company are INTP, BDMN, BBCA, LSIP, ADRO, JSMR, PGAS, LPKR, TLKM, AALI and UNVR categorized as defensive stocks. Keywords: Risk, Return, and Beta of stocks.